A Survey of the Side Effects of Pfizer/BioNTech COVID-19 Vaccine among Vaccinated Adults in Iraq - Abubakir Saleh; Nazar P. Shabila (ACHSM, 2023)
Background: Pfizer-BioNTech vaccine was one of the first vaccines developed for COVID-19 to be used in Iraq. While the benefits of the vaccine outweigh the risks, potential side effects remain major concerns for people and can increase vaccine hesitancy despite usually being short-lasting and mild. This study aimed to evaluate the side effects of Pfizer-BioNTech vaccination among vaccinated adults in Erbil city, Iraq. Methods: A cross-sectional study was carried out with a convenience sample of 401 subjects who received the Pfizer vaccine in nine public healthcare centres in Erbil, Iraq, on February 20th, 2022, and April 17th 2022. Data was collected through interviews with the patients using a questionnaire designed by the researchers; a p-value ≤ 0.05 was considered statistically significant. Results: The prevalence of side effects was 84.4%. Among participants who experienced side effects, the most common was pain at the injection site (93.1% for the first dose and 88% for the second dose). For the first dose, the onset of side effects on the vaccination day (day zero) was reported by 78.9% of those experiencing side effects, and the duration was one day for 45.4% of participants. Severity was rated as mild by 54.3%, and similar results were found for the second dose. Analgesics were used following the first dose by 47% of participants, which resulted in good relief for 96.6% of patients using them, and similar results were found for the second dose. Conclusions: Most participants who received the Pfizer-BioNTech vaccine experienced side effects, the most common of which was pain at the injection site, which was reported for both the first and second doses.